Role Of Behavioural Factors In Asset Pricing: Psychoanalysis Perspective And Evidence From Malaysia - Tuyon, Jasman (2018)
Behavioural finance paradigm argue that behavioural risks are the main driver of stock mispricing that induced stock market inefficiency particularly in emerging Asia and cause unpredicted financial crisis. However, being a new school of thought, the behavioral asset pricing theory and empirical evidence are still incomplete which represents a nascent research area with a multitude of open questions and research opportunities. Based on philosophical lenses of behavioural finance, this thesis discusses alternative theoretical, model, and new evidence on behavioural asset pricing determinants. First and foremost, the alternative theory and model are established. In theory, the psychoanalysis approach is used as an alternative theoretical basis to understand the rational and irrational human behaviours. In modeling, a quasi-rational multifactor asset pricing determinants is proposed that combined rational and irrational sources of equity risks determinants. Firm (EPS, DY, PE) and economic (CI, LEI, LAI) fundamentals are identified as a source of rational risk. While the irrational forces represented by cognitive heuristics (seasonality), and affective biases due to sentiment (BCS, CSI, FKLI) as well as emotion (VOL). In empirical test, this thesis investigates the equity risk and returns properties using behavioural asset pricing ideology in a factor and style investing framework to acknowledge the heterogeneity of risk-return relationships. The empirical tests are performed based on a sample of 238 Malaysian firm stock returns using the panel regression and quantile panel regression methods with monthly data frequency.